From Intention to Behavior in Socially Responsible Investing: Evidence from Young Retail Investors in Indonesia - Michael Susanto; Liliana Inggrit Wijaya; Bertha Silvia Sutejo (Green Publisher Indonesia, 2026)
This study investigates the transition from intention to actual behavior in socially responsible investment (SRI) among young retail investors in Indonesia. Drawing on an extended Theory of Planned Behavior (TPB), the research integrates core TPB constructs— attitude, subjective norms, and perceived behavioral control—with financial literacy and environmental concerns as additional predictors, while incorporating risk propensity as a moderating variable. Using survey data collected from 342 Indonesian retail investors dominated by Generation Z and Millennials, the study employs Structural Equation Modeling (SEM) with SmartPLS 4 to examine both direct and indirect relationships among variables. The results reveal that intention toward SRI plays a central mediating role in shaping actual SRI behavior. Attitude and perceived behavioral control significantly influence intention but do not directly translate into behavior, indicating the presence of an attitude–behavior gap. In contrast, subjective norms exert a significant direct effect on both intention and behavior, highlighting the strong role of social influence in emerging market contexts. Financial literacy and environmental concerns are found to significantly affect both intention and behavior, reinforcing the importance of cognitive capacity and pro- environmental orientation in sustainable investment decisions. Moreover, intention significantly mediates the effects of all antecedent variables on SRI behavior. These findings contribute to the SRI literature by providing empirical evidence from an emerging market and underscore the necessity of strengthening intention formation through social norms, sustainable financial literacy, and supportive investment infrastructure to promote responsible investment behavior among young investors.